New insect pupation chambers (Pupichnia) from the Upper Cretaceous of Patagonia, Argentina - Genise, Jorge Fernando (2007)
Three new records of insect pupation chambers are reported from two localities in the Cretaceous Chubut Group of Patagonia, Argentina: from Sierra Nevada, a new and older ichnospecies of Rebuffoichnus, R. sciuttoi isp. nov. (Coprinisphaeridae), and the first Cretaceous and South American specimens of Pallichnus dakotensis Retallack (Pallichnidae), known until now from a single North American Oligocene locality; from Cañadón Puerta del Diablo, a new type of Rebuffoichnus casamiquelai Roselli that shows some differences from known material of the ichnospecies from the same locality, suggesting a different trace maker. Affinities of P. dakotensis, interpreted originally as a cast of a lined pupation chamber, remain unknown in the light of the new material. Its micromorphology is quite simple, with no constructed wall. R. sciuttoi has a very thinly constructed wall, showing an external texture composed of lobes and fine, helically arranged ridges. Such characters are compatible with those of wasp cocoons. R. casamiquelai, interpreted originally as a coleopteran pupation chamber, has a thickly constructed wall composed of two layers of soil material, showing redistribution of clay and orientation of long grains. Macro- and micromorphology of palaeosols indicate that in both localities pupation occurred in vitric entisols developed on pyroclastic ash-fall deposits on a fluvial floodplain. These new records double the number of the few Cretaceous insect pupation chambers. This is a critical period for understanding the origin and early evolution of building behaviour in insects. Three types of Cretaceous pupation chambers can now be recognized: (1) excavated and lined, e.g. Fictovichnus and Pallichnus (Pallichnidae); (2) constructed mostly with silk, resulting in thin-walled cocoons, e.g. R. sciuttoi (Coprinisphaeridae); (3) constructed mostly with soil material, resulting in thick-walled chambers, e.g., R. casamiquelai (Coprinisphaeridae). A new ethological category, Pupichnia, is proposed for grouping ichnotaxa representing pupation chambers, which, with Calichnia representing nests, comprises the two major types of insect trace fossils in palaeosols.